2009
DOI: 10.1073/pnas.0805375106
|View full text |Cite
|
Sign up to set email alerts
|

FK506-binding protein (FKBP) partitions a modified HIV protease inhibitor into blood cells and prolongs its lifetime in vivo

Abstract: HIV protease inhibitors are a key component of anti-retroviral therapy, but their susceptibility to cytochrome P 450 metabolism reduces their systemic availability and necessitates repetitive dosing. Importantly, failure to maintain adequate inhibitor levels is believed to provide an opportunity for resistance to emerge; thus, new strategies to prolong the lifetime of these drugs are needed. Toward this goal, numerous prodrug approaches have been developed, but these methods involve creating inactive precursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…Next, we confirmed that the corresponding SLF-modified derivative 8 showed a strong (~9-fold) preference for the cellular fraction (Figure 6)35. Remarkably, the FK506-modified derivative 7 was concentrated by more than ~22-fold in the blood cell compartment.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…Next, we confirmed that the corresponding SLF-modified derivative 8 showed a strong (~9-fold) preference for the cellular fraction (Figure 6)35. Remarkably, the FK506-modified derivative 7 was concentrated by more than ~22-fold in the blood cell compartment.…”
Section: Resultssupporting
confidence: 67%
“…We recently reported that appending SLF to an HIV protease inhibitor partitions the resulting molecule into blood cells and prolongs its lifetime 20-fold in vivo 35. Evidence suggests that this improved persistence results from the modified compound being sequestered into the cytoplasm of the blood cells, which is an environment that contains high levels of FKBP but is nearly devoid of the P450 enzymes that metabolize xenobiotics.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The enhanced potency may be a reflection of increased cellular uptake or retention provided by the FK506 group, particularly because FK506 can serve as a substrate and inhibitor of drug efflux transporters such as multidrug resistance protein 1 (41). Notably, the favorable pharmacokinetic properties provided by FK506 have been recently demonstrated for drug conjugates both in vitro and in vivo (42,43). Similarly, conjugation of GR antagonists to bile acids has been explored as a means to target GR antagonism to the liver (28).…”
Section: Discussionmentioning
confidence: 99%